Variability of Internal Wave Strain Over the Western Boundary Region in the North Atlantic - Fan, Liming; Wang, Xin (Frontiers in Earth Science, 2022)
Based on the CTD profiles and mooring measurements of Line W program in the North Atlantic about 35°N/70°W, we investigated the spatial variability of internal wave-induced strain variance along the Line W section and the associated reasons. The results showed that the internal wave strain variance over the slope could be up to 5 times larger than that in the interior. We have validated internal tides (ITs) and near-inertial waves (NIWs) were not the crucial processes for causing this variability. Meanwhile, we found that the high-frequency internal waves generated by interaction of anticylonic eddy and low-frequency internal waves may be a potential cause of strain enhancement. This study implies a potential route of mesoscale eddies to enhance the strain variance induced by internal wave.